The Ascent of Mineralocorticoid Receptor Antagonists in Diabetic Nephropathy - Goenka, Luxitaa; Padmanaban, Raghavan; George, Melvin (Current Clinical Pharmacology, 2019)
Diabetic nephropathy is defined as a decline in the renal function and an increase in the amount of albuminuria (>300 mg/day). The interruption of the renin-angiotensin-aldosterone system (RAAS) by well-established therapies such as angiotensin-converting enzyme inhibitor, angiotensin receptor blockers, calcium channel blockers or diuretics has been beneficial in reducing the progression of renal diseases; however, there is an increase in the levels of aldosterone due to the aldosterone escape phenomenon. Newer and novel approaches to counteract this aldosterone breakthrough while accentuating the anti-hypertensive and anti-proteinuric effects of these agents would be ideal and mineralocorticoid receptor antagonists fit in this slot perfectly. This review attempted to evaluate the safety and efficacy of and mineralocorticoid receptor antagonists for diabetic nephropathy. Presently mineralocorticoid receptor antagonists such as spironolactone, eplerenone and finerenone are being investigated as both monotherapies and as additional therapies. Clinical studies have shown that these drugs have been effective in the reduction of blood pressure, urinaryalbumin- excretion and estimated glomerular filtration rate. The commonly observed adverse effects are hyperkalemia, gynaecomastia and vaginal bleeding, that are bothersome with spironolactone seems to be avoidable if these patients are switched to non-steroidal and mineralocorticoid receptor antagonists such as finerenone and eplerenone. Most of the studies have only evaluated the shortterm effects of mineralocorticoid receptor antagonists on diabetic nephropathy. Hard outcomes such as cardiovascular events, creatinine doubling, progression to end-stage renal disease, mortality and the need for temporary or permanent dialysis need to be studied with these molecules.
Keywords: finerenone